Implementation of Fuzzy Sugeno in the Analysis of the Availability of Split Stone - Siregar, Ari Anshari Yuliansyah; Sriani, Sriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of companies in the industrial sector continues to grow every where. So the level of competition is competitive more increasing. But due to consumer demand that changes, making it a problem serious at the company PT Dexton Mulia Wisesa. especially the demand for split stone. To overcome this problem, a optimization in production quantities so that this does not happen production shortages or excess goods available causing the company to lose. Optimization is possible done by implementing Sugeno fuzzy logic. Sugeno's selection of fuzzy logic is for produce a capable system model estimate the amount of crushed stone inventory. Results from research conducted in July 2023 until June 2024 obtain mape value amounting to 28% and is included in the reasonable category. So it is hoped that in the future, this company can optimize the need for split stone in production.